The Use of Registries Data in Statistical Studies of Employment - Tkachenko, L. H. (Statistics of Ukraine, 2022)
According to the Ministry of Digital Transformation there are more than 350 state registries in Ukraine of which about 200 contain personal information about the population. The creation of registries was based on a narrow departmental approach without due attention to the information value of this resource. The State Statistics Development Programme until 2023 identifies expanding the access of state statistics bodies to administrative data and registries as one of the key areas for reducing the reporting load on respondents. The draft Law of Ukraine “On Official Statistics” (registered by the Verkhovna Rada of Ukraine on September 2, 2021 № 5886) provides an institutional basis for expanding such access for producers of official statistics including to individual registries data. The article aims to reveal the possibilities of using registries data in statistical studies of employment, in particular the data from the registry of insured persons which is administered by the Pension Fund of Ukraine. The scale of information about insured persons is constantly growing but their use for analytical and statistical purposes is still limited. The scale of information about insured persons is constantly growing but their use for analytical and statistical purposes is still limited. Since the beginning of 2021 the quarterly distribution of employees by the number of gross wages has been formed by the registry of insured persons which has significantly reduced the load on respondents of the state statistical observation “Survey of Enterprises on Labor Statistics”. The transition to an alternative data source did not break the general proportions and trends in the distribution of employees by wages groups but increased the dependence of obtaining statistical information on regulatory changes in administrative procedures. Thus, the changes in the form and frequency of companies’ fiscal reporting led to an increase in the waiting period for the publication of the distribution of employees by wage groups by two months. The intensification of the use of registries data in the production of official statistics requires the expansion of the powers of the State Statistics Service of Ukraine for practical participation in the policy for the development of public registries. The registries data of the Pension Fund of Ukraine can significantly expand the list of short-term and additional statistical characteristics of employment and wages especially in terms of structural distributions for the analysis of differentiation and inequality. For in-depth research it is proposed to develop standardized procedures aimed at forming a representative sample of the registries data which will be available in the form of depersonalized microdata to a wide range of researchers.